Literature Review: Characteristics Of Diabetic Foot Ulcer Patients - Annisa Fathiya Muchlis; Andi Kartini Eka Yanti; Nasrah Anastasia Anjani (Sean Institute, 2024)
Diabetic foot begins with the presence of hyperglycemia in diabetic mellitus patients, causing neuropathy and vascular system disorders. There are several risk factors for the occurrence of diabetic foot ulcers, including gender, age and history of DM. This research method was carried out by literature review through the collection of various research journals and 11 samples of related research literature were obtained. The results of the study showed that the characteristics of diabetic foot ulcer patients were predominantly men with the highest age >60 years, the longest duration of suffering from DM was <10 years, and the highest degree of ulcers was degree 4. Age can be associated with the risk of developing diabetic foot ulcers